The Role of Certification Standards in Shaping Halal Supply Chain Practices: A Qualitative Literature Review - Irwan Aufi; Fajar Azhari Julian; Ahmad Maulidizen; Rifqi Fathin Ariaputra; Muhammad Fauzan (Journal of Islamic Law and Legal Studies, 2024)
This study explores the role of certification standards in shaping halal supply chain practices, focusing on their impact on traceability, compliance, and operational efficiency. The primary objective is to examine how standardized halal certifications influence the development of robust and reliable halal supply chains, ensuring adherence to Islamic principles and meeting consumer expectations. Utilizing a qualitative literature review methodology, this research synthesizes findings from academic journals, industry reports, and regulatory guidelines to identify key trends and challenges in the application of halal certification standards. The findings reveal that harmonized global halal standards play a critical role in streamlining trade, enhancing supply chain integrity, and fostering consumer trust. However, inconsistencies in certification criteria across countries and limited cross-border collaboration remain significant obstacles. The study underscores the need for unified certification frameworks, strategic stakeholder engagement, and the adoption of advanced technologies such as blockchain to improve traceability and compliance. The implications of this research highlight the importance of policy reforms and collaborative efforts in strengthening halal supply chain ecosystems, contributing to sustainable growth and global competitiveness in the halal industry.